The viaduct In Calabria as an example of innovative solutions in construction of transport infrastructure - Leniak-Tomczyk, Anna; Łagoda, Grażyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The current legal regulations in the EU and in the world force us to seek new solutions in design and construction of transport infrastructure structure-solutions which comply with the environmental protection rules while being economically justified. The article includes an analysis of innovative solutions in design and construction of transport infrastructure structures in the world using as an example the plans of reconstruction and modernization of a viaduct along A3 highway in Calabria(Italy).